Subaerial biofilms on granitic historic buildings: microbial diversity and development of phototrophic multi-species cultures. Issue 6 (2nd July 2016) - Vázquez-Nion, D.; Rodríguez-Castro, J.; López-Rodríguez, M. C.; Fernández-Silva, I.; Prieto, B.
Abstract: Microbial communities of natural subaerial biofilms developed on granitic historic buildings of a World Heritage Site (Santiago de Compostela, NW Spain) were characterized and cultured in liquid BG11 medium. Environmental barcoding through next-generation sequencing (Pacific Biosciences) revealed that the biofilms were mainly composed of species of Chlorophyta (green algae) and Ascomycota (fungi) commonly associated with rock substrata. Richness and diversity were higher for the fungal than for the algal assemblages and fungi showed higher heterogeneity among samples. Cultures derived from natural biofilms showed the establishment of stable microbial communities mainly composed of Chlorophyta and Cyanobacteria. Although most taxa found in these cultures were not common in the original biofilms, they are likely common pioneer colonizers of building stone surfaces, including granite. Stable phototrophic multi-species cultures of known microbial diversity were thus obtained and their reliability to emulate natural colonization on granite should be confirmed in further experiments.